The entrepreneurial perceptions and motivations of Hungarian students: an empirical study - Farkas, Szilveszter; Koltai, Judit; Lukovszki, Lívia (Marketing & Menedzsment, 2019)
AIMS OF THE STUDY Small businesses and entrepreneurship are one o f the main engines o f the modern economy. Most recently university based start-ups have come very much to the fore because of the increasing difficulties o f the young generation to find an employee position. This study attempts to evaluate the entrepreneurial intentions and ambitions of students by means o f a survey carried out within the student body at two Hungarian universities. METHODOLOGY The key factors - and the scale - of these entrepreneurial ambitions are examined using a complex theoretical model and applying both factor analysis and logistic regression methods. Since regression results proved to provide mixed and hardly interpretable results, a cluster analysis was applied to group students with similar characteristic together. MOST IMPORTANT FINDINGS According to our findings, many Hungarian students have either an inaccurate or inadequate knowledge of the critical factors o f self-employment, the risks involved in a business start-up and even of sources of information. Some students are deterred from becoming an entrepreneur since there are no appropriate role models in their family - hence their lack of information and experience in risk management. Further, most students - even those with a relatively high level of entrepreneurial ambition have very vague ideas about business start-ups, and their business formation plans are simply immature. PRACTICAL SUGGESTIONS This paper presents another piece of evidence that general entrepreneurial intention models can also be applied in Hungary providing a good basis to other comparative studies. A more important implication of our analysis is that university education should focus more on preparing student to entrepreneurial carrier and help them to develop their own business idea during their university studies.